Placental site trophoblastic tumor in the pelvic wall: A case report and review of the literature - Xiao Tang; Fan Yang; Li Jia; Xian-Ying Yao; Kai-Xuan Yang (Wolters Kluwer Medknow Publications, 2013)
Extra-uterine placental site trophoblastic tumor (PSTT) is extremely rare. To our knowledge, PSTT that occurs in the pelvic wall has not yet been reported. A 29-year-old woman presented with amenorrhea and irregular vaginal bleeding of 1 month. A solid tumor mass was detected by ultrasonography in the right pelvic wall. The tumor was comprised of large, polygonal tumor cells, with brisk mitosis and obvious vascular invasion. Immunohistochemical staining demonstrated that tumor cells were positive for human placental lactogen, CD146, cytokeratin, placental alkaline phosphatase, human chorionic gonadotropin were positive, the Ki-67 proliferative index was about 80%. The pathological diagnosis was PSTT. After the operation, the patient was treated with six cycles of etoposide, methotrexate, actinomycin, cyclophosphamide, and vincristine. The patient was followed for 18 months without recurrence. The report shows that extra-uterine PSTT is extremely rare and may have a good prognosis; surgical resection and adjuvant chemotherapy are good options. However, further experience to diagnose and cure this rare tumor is warranted.